The Public Speaking Communication Model of Visually Impaired Massage Therapists in Enhancing Customer Experience in Bandung - Rizki Surya Tawaqal; Ridlwan Muttaqin; Recky Recky (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study is motivated by the need to understand the communication models used by blind massage therapists in delivering their services, as communication plays a crucial role in shaping the customer experience. The research problem focuses on how these public speaking models are manifested and how they influence customer perceptions and satisfaction. A descriptive qualitative method was applied, involving direct observation at Rumah Bugar Sentra Wyata Guna and in-depth interviews with four blind massage therapists. The findings reveal four distinct public speaking communication models: Communicative-Relational, Silent-Reflective, Informative-Educative, and Humorous-Relaxed. Each model contributes differently to the customer experience, ranging from building trust, creating a calm atmosphere, providing additional knowledge, to fostering a cheerful and enjoyable environment. The study concludes that public speaking competence is not merely a complementary skill but a strategic added value that enhances customer satisfaction and strengthens the professional position of blind massage therapists within the health and relaxation service industry